Outcomes of minimally invasive isolated tricuspid valve reoperation after left-side valve surgery: A single-center experience - Liu, Jian; Tan, Tong; Huang, Huanlei; Gu, Wenda; Zang, Xin; Ma, Jianrui; Wu, Hongxiang; Liu, Haozhong; Zhuang, Jian; Chen, Jimei; Guo, Huiming (Frontiers in Cardiovascular Medicine, 2023)
Background Late severe tricuspid regurgitation (TR) after left-side valve surgery (LSVS) is not uncommon. However, the tricuspid valve has been deemed the forgotten valve because the isolated TR is well tolerated with medication, and reoperation has a higher rate of adverse events. With the advancement of minimally invasive techniques, isolated tricuspid valve reoperation (ITVR) via totally endoscopy or transcatheter approach brings the tricuspid valve into spotlight. Our aim is to report the safety and efficacy of minimally invasive ITVR using endoscopic and transcatheter approaches. Methods From October 2020 to October 2021, 21 patients with LSVS history and secondary massive TR underwent minimally invasive ITVR in our institution. Baseline characteristics, surgical outcomes and follow-up results were analyzed, and data between the totally endoscopy approach and the transcatheter approach were compared. Results Of the 21 cases, totally endoscopic isolated tricuspid valve surgery (EITVS) accounts for 16 (76.2%) cases, with 14 tricuspid valvuloplasty cases, and 2 tricuspid valve replacement cases; the remaining 5 (23.8%) cases underwent transcatheter tricuspid valve replacement (TTVR). The mean age was (60.0 ± 8.4) years, with 15 (71.4%) being female. Minimally invasive ITVR procedures were 100% successfully performed in all patients without any perioperative mortality, sternotomy conversion, or reoperation. During the median follow-up of 16.8 months (IQR, 13.0–20.6 months), New York Heart Association Class improved significantly from baseline (P = 0.004). TR severity was significantly improved during postoperative and follow-up period (both P < 0.001). Compared with the EITVS group, the TTVR group had a higher clinical risk score [8.00 (8.00, 9.00) vs. 5.00 (3.25, 5.00), P = 0.001], but a higher success rate in reducing TR to less than grade 1+ (100 vs. 43.8%, P = 0.045) at follow-up. Conclusion In our series, minimally invasive ITVR, including EITVS and TTVR, is a safe and feasible option for severe TR after LSVS, and presents excellent early outcomes in selected patients. TTVR is a reliable alternative for patients with high surgical risk. To improve the results of ITVR, it is necessary to improve patient’s preoperative status or perform reoperation before the onset of significant right heart failure. Further studies with a larger sample size and a longer follow-up period are awaited.